Pinguicula pygmaea (Lentibulariaceae), a new annual gypsicolous species from Oaxaca State, Mexico - Rivadavia, Fernando; Read, Edward Lloyd; Fleischmann, Andreas (Phytotaxa, 2017)
Pinguicula pygmaea (Lentibulariaceae), a new species from the Sierra Madre del Sur of western Oaxaca, Mexico is described and illustrated. The morphological characteristics distinguishing this new species from other similar species are discussed, together with its distribution and ecology.